Analysis of Efficient Control Strategy for Wind Farm Using Converters - K., Sivasantosh kumar; R., Puviarasi (International Journal of Psychosocial Rehabilitation, 2020)
Wind energy has been one of the most important and promising green energy options in recent years and demands that greater grid reliability during and after grid disruptions be sustained. This project deals with improving the efficient control strategy of a wind farm using converters both during fault and removal of fault conditions. By the use of converters and crowbars, the whole system is protected even during fault conditions. By using better means of converters, the reactive power is improved in the overall system. Using variable-speed wind turbine turbines, the main benefit of speed control is usually configured to give optimum power. The goal of this project is to achieve an effective control strategy for improving the low voltage drive (LVRT), which uses converters based on its merits in the Doubly Fed Induction Generator (DFIG).